Monitoring transmissibility and mortality of COVID-19 in Europe. (June 2020) - Yuan, Jing; Li, Minghui; Lv, Gang; Lu, Z. Kevin
Highlights: As of March 10, 2020, Italy had reported 9172 COVID-19 cases with 463 deaths. We report the real-time reproductive numbers ( R ( t )) and case fatality rates for selected European countries (Italy, France, Germany, and Spain) by March 9, 2020. The R ( t ) was greater than 2 in the selected European countries, indicating that the outbreak will continue. Abstract: Objectives: As a global pandemic is inevitable, real-time monitoring of transmission is vital for containing the spread of COVID-19. The main objective of this study was to report the real-time effective reproduction numbers ( R ( t )) and case fatality rates (CFR) in Europe. Methods: Data for this study were obtained mainly from the World Health Organization website, up to March 9, 2020. R ( t ) were estimated by exponential growth rate (EG) and time-dependent (TD) methods. 'R0' package in R was employed to estimate R ( t ) by fitting the existing epidemic curve. Both the naïve CFR (nCFR) and adjusted CFR (aCFR) were estimated. Results: With the EG method, R ( t ) was 3.27 (95% confidence interval (CI) 3.17–3.38) for Italy, 6.32 (95% CI 5.72–6.99) for France, 6.07 (95% CI 5.51–6.69) for Germany, and 5.08 (95% CI 4.51–5.74) for Spain. With the TD method, the R value for March 9 was 3.10 (95% CI 2.21–4.11) for Italy, 6.56 (95% CI 2.04–12.26) for France, 4.43 (95% CI 1.83–7.92) for Germany, and 3.95 (95% CI 0–10.19) for Spain. Conclusions: This study provides important findings on the early outbreak of COVID-19 in Europe. Due to the recent rapid increase in new cases of COVID-19, real-time monitoring of the transmissibility and mortality in Spain and France is a priority.